Particle flow simulation of Brazilian splitting failure characteristics of layered shale - Feng Sun; Wei Huang; Bingbing Zhao; Shifeng Xue; Bo Zhou (Journal of Petroleum Exploration and Production Technology, 2023)
Abstract Shale reservoir is the research hotspot in the development of unconventional oil and gas resources. The properties of bedding plane have an important influence on the mechanical behavior of shale. According to the fracture characteristics of layered shale under Brazilian splitting load, the effects of bedding angle, bond strength ratio and natural fractures on the tensile strength and fracture pattern of layered shale in Brazilian splitting test were studied by particle flow code. The evolution mechanism of meso–macro fracture of shale is analyzed by combining the dynamic change process of particle mesoscopic force chain and crack. The results show that three types of fracture patterns are observed: splitting tensile failure of shale matrix, splitting tensile failure along bedding plane and tensile–shear composite failure along shale matrix and bedding plane. Mesoscopic cracks initiate at the top and bottom loading points of the disk. After the peak load, mesoscopic cracks propagate through and appear dense force chains until macroscopic failure occurs. The bond strength ratio of bedding plane affects the failure pattern and peak strength of the specimen. With the increase in bedding angle, the tensile strength decreases gradually. Considering the influence of natural fractures, the tensile strength of shale is lower, and the crack propagation is more complex. The research model and results provide theoretical basis for the mechanical properties evaluation and fracture pattern analysis of shale.